A Comprehensive Review of FDG PET Incidentalomas: Their Diagnosis, Clinical Significance, and Management. (15th September 2017) - Banks, Kevin; Carra, Bradley; Wolin, Ely
Abstract : Fluorodeoxyglucose positron emission tomography (FDG PET)-CT takes advantage of the fact that many malignancies are hypermetabolic and accumulate the positron-emitting glucose analog, F18-FDG. The increased accuracy of FDG PET-CT in the diagnosis, staging, and surveillance of many cancers has made it a mainstay in oncologic imaging. Unfortunately, FDG uptake can be encountered in a wide array of benign processes; and thus, given the whole body technique inherent to these examinations, radiologists frequently encounter indeterminate metabolic findings on these complex examinations. These unexpected hypermetabolic foci are sites of significant FDG uptake that are unlikely to be related to the primary neoplasm yet have been found to represent an occult second malignancy in up to 4% of instances.1 Thus, it can be very challenging to determine the importance of incidental metabolic findings found on PET-CTs. The potential clinical risk placed on these indeterminate findings by the radiologist has considerable influence on further evaluation and management. This article provides a comprehensive review of FDG-avid incidentalomas, their mimics, and evidence-based information of the clinical implications of these abnormalities.